การประมาณค่าความผันผวนและการพยากรณ์ผลตอบแทนของการลงทุนหมวดพัฒนาอสังหาริมทรัพย์ ในตลาดหลักทรัพย์แห่งประเทศไทย: Estimation of Volatility and Return of Property Development Companies in the Stock Exchange of Thailand - บุญวัฒน์ เกรียงไกร; วรรณศิลป์ วรรณกิตติ์ (Journal of Applied Economics and Management Strategy, 2018)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาเปรียบเทียบการใช้แบบจำลอง GARCH-Mและ OLS เพื่อประมาณค่าเบต้าจากทฤษฎี Capital Asset Pricing Mode l (CAPM) และนำค่าเบต้าที่ได้จากแบบจำลองทั้งสองอันไปสร้างเส้น Security Market Line (SML) เพื่อพิจารณาความน่าลงทุนของแต่ละหลักทรัพย์ โดยข้อมูลที่นำมาใช้ในการศึกษาเป็นข้อมูลทุติยภูมิ ซึ่งเป็นข้อมูลราคาปิดรายวันของหลักทรัพย์ 10 อันดับแรก ในกลุ่มอสังหาริมทรัพย์ที่มีการซื้อขายสูงสุด ในระยะเวลา 5 ปี เริ่มตั่งแต่ 4 มกราคม 2553 ถึง 30 ธันวาคม 2558 ผลการเปรียบเทียบผลตอบแทนของหุ้นแต่ละตัวกับผลตอบแทนที่เหมาะสมที่มีการปรับด้วยความเสี่ยงพบว่า จากแบบจำลอง GARCH-M มีหลักทรัพย์ที่มีราคาซื้อขายต่ำกว่ามูลค่าที่เหมาะสม (น่าลงทุน)ได้แก่ BLAND, ITD, PS, SPALI และ LPN เทียบกับผลจากแบบจำลอง OLS ซึ่งมีเพียงหลักทรัพย์เดียวคือBLAND ที่มีราคาต่ำกว่ามูลค่าที่เหมาะสม (น่าลงทุน) ทั้งนี้ ผู้วิจัยเห็นว่า ค่าเบต้าจากแบบจำลอง GARCH-Mน่าจะมีความน่าเชื่อถือมากกว่าค่าเบต้าที่ได้จากแบบจำลอง OLS เนื่องจากเป็นที่ยอมรับกันโดยทั่วไปว่าความผันผวนของราคาและผลตอบแทนของหลักทรัพย์มีลักษณะผันแปรตามกาลเวลา (Time-varying Volatility) และผลตอบแทนที่คาดหวังของหลักทรัพย์จะสะท้อนค่าความผันผวนของตนเอง ซึ่งสอดคล้องกับรูปแบบของแบบจำลอง GARCH-M The objective of this paper is to study and compare the use of GARCH-M model and OLS model to estimate the CAPM-beta. Then the estimated beta values from the two models were used to construct the Security Market Line (SML) in order to determine investment worthiness of the selected companies in the Stock Exchange of Thailand. The data used are the closing prices of 10 most-actively-traded stocks of real estate companies listed in the Stock Exchange of Thailand. The data covers the period of 5 years from 4th January 2010 to 30th December 2015. According to the comparision of the return of each share with the required (risk-adjusted) return, it finds that using betas from GARCH-M model results in the shares BLAND, ITD, PS, SPALI and LPN being under-valued (worthy to invest). On the other hand, when the betas from OLS model were used, only the share BLAND was under-valued. In this respect, the researchers are of opinion that the betas calculated from GARCH-M model should be more reliable for use than the betas derived from OLS model since it is generally accepted that the volatility of stock price and return are time-varying and that the expected return of the share will reflect such volatility in investment decision in which the GARCH-M model could better address such statistical behavior.